Literature review dari randomized controlled trials (RCTs): Pengaruh prebiotik terhadap sistem kekebalan usus penderita diabetes mellitus tipe 2 - Tiara Permatasari; A'immatul Fauziyah (Poltekkes Kemenkes Aceh, 2024)
Background: The gut microbiome, plays a crucial role in maintaining overall health. An imbalance in the microbiome (dysbiosis) can lead to various health issues, including type 2 diabetes. Prebiotics, as nutrients for gut microflora, have the potential to reduce dysbiosis and enhance gut immunity in type 2 diabetes patients. However, there is still limited research on the effects of prebiotics on gut immunity in individuals with type 2 diabetes.Objectives: To asses the effect of prebiotics on the gut immune system in patients with type 2 diabetes.Methods: A systematic literature review was conducted using the PRISMA method, including full-text RCT articles from 2014-2024. Databases searched included PubMed, Scopus, MDPI, and Elsevier.Results: Studies show prebiotics significantly influence gut microbiota composition, especially increasing Bifidobacterium in type 2 diabetes patients, though overall diversity remained unchanged due to short study durations.Conclusion: Prebiotics enhance gut microbiota, particularly Bifidobacterium, in type 2 diabetes patients. This increase, along with the production of SCFAs, plays a role in lowering gut pH, supporting the growth of beneficial bacteria, and inhibiting pathogens. These findings suggest the potential of prebiotics as part of type 2 diabetes management; however, further research is needed to confirm their clinical application. Healthcare institutions are encouraged to develop educational programs emphasizing the importance of gut microbiota and the role of prebiotics in the health of type 2 diabetes patients.